Specific cultivation-independent enumeration of viable cells in probiotic products using a combination of fluorescence in situ hybridization and flow cytometry - Snaidr, Laura; Mühlhahn, Peter; Beimfohr, Claudia; Kreuzer, Christian; Richly, Carolin; Snaidr, Jiri (Frontiers in Microbiology, 2024)
This study introduces an optimized integration of flow cytometry and Fluorescence In Situ Hybridization (Flow-FISH) as an approach for the specific enumeration of gram-positive bacteria in probiotic products, overcoming the limitations of conventional methods. The enhanced Flow-FISH technique synergizes the rapid and automated capabilities of flow cytometry with the high specificity of FISH, facilitating the differentiation of viable cells at the species level within probiotic blends. By analyzing lyophilized samples of Lacticaseibacillus rhamnosus, Lactiplantibacillus plantarum and Bifidobacterium animalis subsp lactis, and a commercial product, the study highlights the optimized Flow-FISH protocol's advantages, including reduced hybridization times to 1.5 hours and elimination of centrifugation steps.Comparative evaluations with the widely accepted enumeration methods plate count and Live/Dead (L/D) staining were conducted. The study revealed that Flow-FISH produces higher viable cell counts than plate count, thereby challenging the traditional "gold standard" by highlighting its predisposition to underestimate actual viable cell numbers. Against L/D staining, Flow-FISH achieved comparable results, which, despite the different foundational premises of each technique, confirms the accuracy and reliability of our method.In conclusion, the optimized Flow-FISH protocol represents a significant leap forward in probiotic research and quality control. This method provides a rapid, robust, and highly specific alternative for the enumeration of probiotic bacteria, surpassing traditional methodologies. Its ability to enable a more detailed and reliable analysis of probiotic products paves the way for precise quality control and research insights, underscoring its potential to improve the field significantly.